Optical Properties of the Semiconductor Nanoclusters - Kovalchuk, Volodymyr; Popriaha, Diana (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The paper presents the results of the study of the influence of external factors on the change in the morphology of nanoclusters in a matrix environment. Effective methods for calculating the optical characteristics of quantum-scale systems - semiconductor nanoclusters are highlighted. The prospect of combining theoretical methods of computer modeling (within the framework of molecular dynamics) with experimental studies of semiconductor nanoclusters in a matrix environment is illustrated.